Romanian Market-The Transition Period - Irinoiu, Manuela (My University, 1999)
The study aims at the understanding of the change in market structure in Romania after the revolution in 1989. Therefore, the content of the study includes the social, economical, political and cultural situation after December 1989 up to now. The study includes the literature on related issues and a survey on Romanian market conducted in March 1999. This study consists of four chapters along with introduction and conclusion. In introduction, the problems are described in a general framework and the objectives and the importance of the study are outlined. In the first chapter, the situation before the collapse of socialism is described in economical, sociological and political aspects. The needs and the effects of the transition from common market to a market economy are investigated. The second chapter emphasises the importance of the national interest and inquires the present structure of the Romanian market with respect to the national interest. The third chapter is based on the need of Romania's own economic model. It underlines the necessity of a market economy in the country but also speaks about the form of this new economic model. The last chapter is reserved for the survey conducted on 85 respondents in March 1999 in Bucharest, Romania.
Keywords: Genel yönetim; PAZARLAMA; Pazarlama yönetimi